American Dream as Revealed Through the Character of Matthew in the Movie of Fatherhood (2021) - Setiani, Rita; Hidayah, Atinia (Metaphor, 2024)
This study is aimed to analyze : (1) The concept of the American Dream reflected in the character Matthew in the Fatherhood (2021) , (2) The social and economi factors influence the journey of Matthew character in achieving the vision of the American Dream in the Fatherhood (2021) film. The study uses a descriptive qualitative method to analyze the film entitled Fatherhood (2021) directed by Paul Weitz as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by using displaying, explaining, selecting, and interpreting. The researcher analyzes the data by using theory of popular culture of American Dream. The result of the study : (1) The concept of the American Dream reflected in the character Matthew in the Fatherhood film such as hard work and resilience, family and community support, providing the best education for the childern, happiness and family unity, and courage in facing challenges; (2) The social and economi factors influence the journey of Matthew character in achieving the vision of the American Dream in the Fatherhood film include family and friends support, social stigma, community role, employment status and income, access to education and training.